Perilaku Perusahaan Multinasional dan Aggressive Transfer Pricing Practices Terhadap Kepatuhan Pembebanan Biaya Promosi (Studi Kasus Kasus PT MSM) - Supriyadi Supriyadi (Majalah Ilmiah Bijak, 2019)
This research aimed to analyze Multinational Enterprises behavior and aggressive transfer pricing practices that compliance of promotion expenses (Case Study PT MSM). First, to analyze formal compliance of promotion expenses on MNEs. Second, to analyze material compliance of promotion expense on MNEs. Third, to analyze economic benefits for PT MSM and MNEs.The research approach used is descriptive qualitative with data collection through in-depth interviews with informations determinded by Account Representative of the Tax Sercive Office B that handles PT MSM. The research instrument is the data and information collection through interview dan documentation. This reseach  is used MNEs theory and compliance theory.The research results show that: first, promotion expenses on MNEs that Case Study PT MSM reach about Rp 3,2triliun from fiscal year about 2003 until 2016 average 20% form sales.  For formal compliance analysis for promotion expenses for PT MSM is comply with Ministry of Finance Regulation number 02/PMK.03/2010 about promotion expenses with attaching nominative list of promotion expenses. Second, for material compliance analysis of promotion expenses is not directly related for PT MSM, to promote MNEs. Third, promotion expenses that paying PT MSM gives economic benefit  for promotion of MNEs. Therefore PT MSM  should get renumeration because of  its function, assets and risks.